Race day - Tuchman, Gail. (Washington, D.C. : National Geographic, 2010)
Young readers are invited along on an automobile race, where they can see what it is like to race, take pit stops, and zoom around other cars.
"National Geographic kids"-- Cover.
"For kids who are ready to read"--Cover.
Keywords: Automobile racing -- Juvenile literature; Automobile racing; Readers; Readers (Primary)